Manipulation of the diet–microbiota–brain axis in Alzheimer’s disease - Lee, Daniel; Lee, Virginia M-Y.; Hur, Seong Kwon (Frontiers in Neuroscience, 2022)
Several studies investigating the pathogenesis of Alzheimer’s disease have identified various interdependent constituents contributing to the exacerbation of the disease, including Aβ plaque formation, tau protein hyperphosphorylation, neurofibrillary tangle accumulation, glial inflammation, and the eventual loss of proper neural plasticity. Recently, using various models and human patients, another key factor has been established as an influential determinant in brain homeostasis: the gut–brain axis. The implications of a rapidly aging population and the absence of a definitive cure for Alzheimer’s disease have prompted a search for nonpharmaceutical tools, of which gut-modulatory therapies targeting the gut–brain axis have shown promise. Thus, multiple recent studies examining changes in human gut flora in response to various probiotics and environmental factors are limited and difficult to generalize; whether the state of the gut microbiota in Alzheimer’s disease is a cause of the disease, a result of the disease, or both through numerous feedback loops in the gut–brain axis, remains unclear. However, preliminary findings of longitudinal studies conducted over the past decades have highlighted dietary interventions, especially Mediterranean diets, as preventative measures for Alzheimer’s disease by reversing neuroinflammation, modifying the intestinal and blood–brain barrier, and addressing gut dysbiosis. Conversely, the consumption of Western diets intensifies the progression of Alzheimer’s disease through genetic alterations, impaired barrier function, and chronic inflammation. This review aims to support the growing body of experimental and clinical data highlighting specific probiotic strains and particular dietary components in preventing Alzheimer’s disease via the gut–brain axis.